ANALISIS KINERJA PENYULUH PERTANIAN DALAM MEMBERDAYAKAN DAN MEMANDIRIKAN PETANI PADI (Oryza Sativa) SAWAH DI KELURAHAN KEMPAS JAYA KECAMATAN KEMPAS KABUPATEN INDRAGIRI HILIR - Jalaluddin Jalaluddin; Gerhana Adjie (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2020)
The Kempas District is one of the area that has the opportunity to develop food commodities, namely rice, especially wet rice. The rice productivity of Kempas District is higher than other districts in Indragiri Hilir Regency with a productivity yield of 39.96 kw / ha with an area of 2,300 ha. This study aimed to (1) determine the performance of agricultural instructors; (2) find out the level of farmer empowerment and farmer independence. This research was carried out in Kempas Jaya Village, Kempas District, Indragiri Hilir Regency for three months, October 2017 - December 2017. The type of data used in this study are primary data and secondary data. Primary data were obtained from interviews and questionnaires. Secondary data were obtained from information related to agricultural extension in Kempas District and online journals. The research method is quantitative through 30 rice farmers in Kempas Jaya District. Analysis of the data used in this study is descriptive analysis with a Likert scale. The results showed (1) the performance of extension workers in Kempas Jaya was "quite good" with a percentage of 73.3%; (2) the level of empowerment of farmers in Kempas Jaya village is "very empowered" with a percentage of 60.0% and the independence of farmers in Kempas Jaya village is "Very Independent" with a percentage of 60.0%.